Health Information Seeking Behaviour of Rural Women in Ekiti State, Nigeria: Implications for Librarians - Ajibare, Oluwaseun O.; Adeniran, Ayobami (Communicate: Journal of Library and Information Science, 2023)
The health information seeking behaviour of individuals inevitably contributes to how they prevent illnesses or cope with disease burden. This study examined the health information seeking behaviour (HISB) of rural women in Ekiti State, Nigeria. A cross sectional survey design was adopted and the population is 817,843 rural women in Ekiti State, Nigeria. Multistage sampling technique was used to select 402 respondents. Questionnaire was used for data collection and descriptive statistics was used for data analysis. Findings revealed that rural women needed information relating to various illnesses and diseases, and also to take care of their family. These women sourced the needed health information mostly from friends, radio and traditional healers. The library was ranked among the lowest source of health information. Also, the women used the health information sought for various preventive and curative purposes. Findings from this study imply that the few existing libraries in the rural areas are not being fully utilised by the women. It is recommended that librarians in the public libraries should design information services to meet the health information needs of rural women in the community.